1993
DOI: 10.1007/bf00004020
|View full text |Cite
|
Sign up to set email alerts
|

Agglutinins from marine macroalgae of the southeastern United States

Abstract: Protein extracts from 22 species of marine macroalgae from Florida and North Carolina were compared for their abilities to agglutinate sheep and rabbit erythrocytes. Protein extracts from 21 algal species agglutinated rabbit erythrocytes compared to 19 for sheep erythrocytes. However, agglutination by brown algal extracts was variable. The agglutination produced by protein extracts from Dictyota dichotoma could be blocked by addition of polyvinylpyrrolidone. Protein extracts from North Carolina macroalgae were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…It is these protein-carbohydrate interactions that are responsible for lectin involvement in numerous biological processes such as host-pathogen interactions, cell-cell communication, induction of apoptosis, cancer metastasis and differentiation, as well as recognising and binding carbohydrates (Hori et al 2000). Furthermore, lectin has been found to increase the agglutination of blood cells (erythrocytes) and is also useful in the detection of diseaserelated alterations of glycan synthesis, including infectious agents such as viruses, bacteria, fungi and parasites (Bird et al 1993;Cardozo et al 2007;Murata and Nakazoe 2001). Other bioactive properties exhibited by marine algal lectins include antibiotic, mitogenic, cytotoxic, anti-nociceptive, anti-inflammatory, anti-adhesion and anti-HIV activities (Bird et al 1993;Mori et al 2005;Smit 2004).…”
Section: Proteinsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is these protein-carbohydrate interactions that are responsible for lectin involvement in numerous biological processes such as host-pathogen interactions, cell-cell communication, induction of apoptosis, cancer metastasis and differentiation, as well as recognising and binding carbohydrates (Hori et al 2000). Furthermore, lectin has been found to increase the agglutination of blood cells (erythrocytes) and is also useful in the detection of diseaserelated alterations of glycan synthesis, including infectious agents such as viruses, bacteria, fungi and parasites (Bird et al 1993;Cardozo et al 2007;Murata and Nakazoe 2001). Other bioactive properties exhibited by marine algal lectins include antibiotic, mitogenic, cytotoxic, anti-nociceptive, anti-inflammatory, anti-adhesion and anti-HIV activities (Bird et al 1993;Mori et al 2005;Smit 2004).…”
Section: Proteinsmentioning
confidence: 96%
“…Furthermore, lectin has been found to increase the agglutination of blood cells (erythrocytes) and is also useful in the detection of diseaserelated alterations of glycan synthesis, including infectious agents such as viruses, bacteria, fungi and parasites (Bird et al 1993;Cardozo et al 2007;Murata and Nakazoe 2001). Other bioactive properties exhibited by marine algal lectins include antibiotic, mitogenic, cytotoxic, anti-nociceptive, anti-inflammatory, anti-adhesion and anti-HIV activities (Bird et al 1993;Mori et al 2005;Smit 2004). Lectins from three Eucheuma species, E. serra, E. amakusaensis and E. cottonii have shown strong mitogenic activity on mouse and human lymphocytes, whilst a marine glycoprotein E. serra agglutinin (ESA) derived from E. serra exhibits a cytotoxic effect against several cancer cell lines, such as colon cancer Colo201 cells and cervical cancer HeLa (Kawakubo et al 1997(Kawakubo et al , 1999Sugahara et al 2001).…”
Section: Proteinsmentioning
confidence: 96%
See 1 more Smart Citation
“…The occurrence of hemagglutinins in extracts of marine algae was first described by Boyd et al (1966), and subsequent studies have reported the widespread distribution of lectins from several algal species (Blunden et al 1975;Fabregas et al 1985;Hori et al 1988;Bird et al 1993;Freitas et al 1997). Seasonal variations in hemagglutinating activity of lectins from marine algae have been detected for the red algae Gracilaria verrucosa (Takahashi and Katagiri 1987), G. domigensis, Gelidium pusillum (Benevides et al 1999), and the green alga Ulva lactuca (Sampaio et al 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Since, there have been many surveys on distribution of hemagglutinins in marine macroalgae, including those from English (Blunden et al 1975(Blunden et al , 1978Rogers et al 1980), Japanese (Hori et al 1988), Spanish (Fábregas et al 1985(Fábregas et al , 1992, United States (Chiles and Bird 1989;Bird et al 1993), Brazilian (Ainouz and Sampaio 1991;Ainouz et al 1992;Freitas et al 1997), Pakistani (Alam and Usmanghani 1994), Chinese (Zheng and Lu 2002), Vietnamese (Hung et al 2009a), Indian (Kumar and Barros 2010), and Antarctic marine algae (Souza et al 2010), more than 250 algal species have so far been reported to contain hemagglutinins, but the number of these proteins (lectins) purified and characterized is still small in comparison to lectins from higher plants. Characterization studies reveal that algal lectins differ from higher plant lectins in a variety of properties.…”
Section: Introductionmentioning
confidence: 98%